Analysis of application of heat loss recovery system using organic Rankine сycle for drive of process equipment - A. M. Kalashnikov; A. A. Kapelyukhovskaya; I. D. Obukhov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The analysis of heat exchange processes during cooling of the heated surface of the process equipment is carried out on the basis of the equations contained in the ANSYS Fluent package. When modeling heat exchange processes, the following boundary conditions are adopted: the temperature of the heated surface; the coil heat exchanger is located at a distance from the heated surface of the process equipment. From these results, we can draw the following conclusions: the increase in the temperature of the heated surface leads to the increase of the heating zone of the refrigerant with high capacity and, hence, to increase heat capacity; increasing the refrigerant flow rate, the lower the temperature of the refrigerant at the exit, but increases the thermal capacity; increasing the pressure of the heated refrigerant increases the thermal; this design of the heat exchanger allows you to achieve the necessary power for the operation of the drive by: changing the flow rate of the refrigerant, the excess pressure of the refrigerant, the number of elbows, as well as by installing a heat-reflecting casing